2013
DOI: 10.1155/2013/461409
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Incidentalomas in Cancer Patients Are Not Always “Innocent”: A Case Report and Review of the Literature

Abstract: Herein, we report an unusual case of a 78-year-old woman with synchronous presentation of sigmoid cancer and a nonfunctioning primary adrenal cortex carcinoma, who developed superior vena cava syndrome due to metastatic lymphadenopathy from the latter malignancy. Our case suggests that adrenal incidentalomas during initial staging evaluation after cancer diagnosis are not always “innocent” and should not be “a priori” considered incidental findings attributed to hyperplasia, adenoma or even a non life-threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Synchronous colorectal and adrenocortical carcinoma has been described twice in the literature. Economopoulou et al 15 reported two case series in which patients with colon cancer underwent an adrenalectomy and one patient was found to have adrenocortical carcinoma. Karamurzin et al 16 reported a patient with Lynch syndrome, who was found to have an adrenocortical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous colorectal and adrenocortical carcinoma has been described twice in the literature. Economopoulou et al 15 reported two case series in which patients with colon cancer underwent an adrenalectomy and one patient was found to have adrenocortical carcinoma. Karamurzin et al 16 reported a patient with Lynch syndrome, who was found to have an adrenocortical carcinoma.…”
Section: Discussionmentioning
confidence: 99%